Variações climáticas regionais, produtividade e uso de defensivos agrícolas e produtos de controle biológico no cultivo da soja - Machado, Marcos Vinicius Muniz (2023)
Monitoring weather conditions during the soybean cycle is essential in agricultural planning. The variation of these conditions, such as temperature, relative humidity (RH), precipitation, and wind speed, influences the amount of pesticides and biological control products applied, the quality of spraying and, consequently, the emergence of pests, diseases and weeds, as well as the productive performance of soybeans. Thus, the application of agricultural pesticides and biological control products is an agricultural operation of great importance in soybean production, as it provides the control or eradication of pests, diseases, and invasive plants that compete with the crop for the same natural resources, and this application is highly dependent on weather conditions. The research was carried out in a commercial area with 15.5 ha, located in the municipality of Céu Azul in the state of Paraná, Brazil. The objective of this work was to establish the correlation between meteorological conditions and soybean productivity in the 2017/2018, 2018/2019 and 2019/2020 harvests; and also obtain the relationship between weather conditions and the use of agricultural defensives and biological control products, carrying out the survey of weather conditions and preparing the economic survey of the use of agricultural defensives and biological control products in the agricultural harvests of 2020/2021 and 2022/2023. Regarding the results, the soybean productivity obtained in the area in the 2019/2020 harvest was 3.727 t ha¯¹, higher than the other two harvests, with the 2018/2019 harvest reaching the lowest value, 2.394 t ha¯¹, occurrence of precipitation outside the recommended and drought, indicating the influence of weather on the productivity obtained. With regard to spraying in the 2020/2021 harvest, a greater amount of agricultural pesticides and biological control products were used when compared to the 2022/2023 harvest, attesting to the possible influence of weather variation. Comparing the monetary value spent on agricultural pesticides and biological control products, the 2020/2021 harvest reached expenses were significantly higher than the 2022/2023 harvest.